European Society of Intensive Care Medicine и Society of Critical Care Medicine: 6 key provisions for management of sepsis patients. Where do we go next? - V. A. Rudnov; V. A. Bagin; M. N. Аstafieva (Вестник анестезиологии и реаниматологии)
The objective: to analyze the validity of recommendations of the special research committee of the European Society of Intensive Care Medicine (ESICM) and Society of Critical Care Medicine (SCCM) concerning the most important provisions for the management of patients with sepsis and septic shock identifying predictors of long-term need for medical care and lethality.Subjects and methods. The article analyses the publications based on which experts in sepsis management identified the key provisions of the above recommendations.Results. Attention is focused on six issues: empirical combined antibiotic therapy, individual infusion volume, express diagnosis of infection, assessment of organ and systemic dysfunction, identification of predictors of long-term need for medical care and lethality, and implementation attempts and prospects of precise/personalized medicine. It has been shown that the values of SOFA score, heart rate, syst. blood pressure, lactate and albumin levels should reflect the balance of the groups in these parameters. Molecular classification of patients with sepsis providing different endotypes allows better patients enrollment in clinical trials.